The trinomial health, safety and happiness promote rural tourism - Rafael Robina-Ramírez; Rafael Ravina-Ripoll; Francisco Javier Castellano-Álvarez (BMC Public Health, 2023)
Abstract Background Health and safety protocols have become a requirement to promote rural tourism (PRT). From this perspective, this paper empirically analyses how the health and safety dimensions influence the happiness of hotel managers and rural tourists in the post-Covid 19 era. Methods A theory-based structural equation model will be carried out of activation of norms, that measure variables: sanitary, socioeconomic, and safety. Precisely, we will measure how those three attributes affect the managers-guests’ health in rural areas and their search for happiness at the rural destination. Based on the above, a field of study has been 215 rural tourist accommodations in the Extremadura region (Spain) and a sample population of 443 guests. Data were organised through the SEM-PLS path modelling. Results The results achieved statistically show the need to undertake a new model of healthier and safer tourism consumption that values the tourist resources of rural areas, especially nearby and sustainable destinations, based on the guiding principles of safety, health, and happiness. Conclusions The first conclusion is that promoting tourist destinations under safe and healthy conditions has become a priority objective in the tourism industry. The second conclusion that follows from the first is that the variables safety and health and the pursuit of happiness are essential factors in promoting tourist destinations for rural hotel managers and rural tourists. The third conclusion related to the first two is that the opportunity that this study provides to develop strategies of an innovative, sustainable, and creative nature based on the relationships of the new trinomial of health, safety and happiness, from the perspective of happiness management.